POLFEL - Free Electron Laser in Poland - Romaniuk, Ryszard S. (Photonics Letters of Poland, 2009)
Free electron laser in Poland ? POLFEL is a coherent light source of the IVth generation, characterized by very short pulses in the range of 10-100fs, of big power 0,2GW and UV wavelength of 27nm of average power 1W, with effective high power third harmonic of 9nm. The laser consists of a linear superconducting accelerator 100m in length, undulator and experimental lines. It generates a monochromatic and coherent radiation and can be tuned from THz range to UV. The linac works in quasi-CW or real-CW mode. It is planned by XFEL-Poland consortium as a part of the ESFRI priority EuroFEL infrastructure collaboration network, part of the ERA